The Role of Word of Mouth, Peers, and Promotion on the Decision to Exercise at Gymnasiums in Bandar Lampung City with Hedonic Motivation as a Mediating Variable - Utami Pratiwi; Lestari Wuryanti; Ayu Nursari (International Journal of Economics and Management Sciences, 2026)
This study examines the effects of word of mouth, peer influence, and promotion on exercise decisions at gymnasiums in Bandar Lampung City, with hedonic motivation as a mediating variable. Drawing on the Theory of Planned Behavior and consumer behavior perspectives, the research employed a quantitative causal-associative design. Data were collected through structured questionnaires from 100 active members of four gymnasiums and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS . The results indicate that word of mouth, peer influence, and promotion have positive and significant effects on hedonic motivation and on exercise decisions. Hedonic motivation also exerts a positive and significant effect on exercise decisions, suggesting that pleasurable and emotionally rewarding fitness experiences reinforce consumers' intention to engage in regular gym- based exercise. Mediation analysis further reveals that hedonic motivation significantly channels the effects of peer influence and promotion on exercise decisions, while the indirect effect of word of mouth is also significant, although its negative coefficient warrants careful interpretation. These findings demonstrate that exercise decisions are shaped not only by utilitarian health considerations but also by social influence, promotional exposure, and affective consumption experiences. The study provides practical insights for gym managers in designing service and marketing strategies that strengthen customer engagement and sustained participation.